The Impact of Transformational Leadership on Organizational Ambidexterity in Jordanian Pharmaceutical Companies: The Mediating Role of Managerial Empowerment - ALkhawaldah , Reyad A.; ALshaer, Sawsan A.; Atieh, Musa A.; ALshalabi , Feras S.; ALatyat , Zakarya A. (Jordan Journal of Business Administration, 2025)
This study aims to explore the impact of transformational leadership on organizational ambidexterity in Jordanian pharmaceutical companies, focusing on the mediating role of managerial empowerment. The study was designed using a quantitative methodology, with data collected from 201 employees working in Jordanian pharmaceutical companies. A questionnaire was developed to measure three key variables: transformational leadership, managerial empowerment, and organizational ambidexterity with its dimensions (exploration, exploitation, and structural ambidexterity). The results indicated that transformational leadership significantly and positively impacts managerial empowerment, with a statistically significant path coefficient. Additionally, the findings showed that managerial empowerment strongly influences organizational ambidexterity and mediates the relationship between transformational leadership and organizational ambidexterity. Furthermore, transformational leadership was found to significantly impact the exploration and exploitation dimensions of organizational ambidexterity, while its effect on structural ambidexterity was less pronounced. The study contributes theoretically by enhancing understanding of the complex relationships between transformational leadership, managerial empowerment, and organizational ambidexterity. It also offers practical recommendations for pharmaceutical companies to strengthen transformational leadership and empower employees to improve organizational performance, increase innovation, and capitalize on opportunities. One of the study’s main limitations is its focus on a single sector and quantitative methodology without qualitative approaches. Therefore, the study recommends further research in other industries and applying qualitative methods to gain deeper insights into these relationships.